Guía para la traducción de : a propósito de la lógica de no-todo fálico - Marqués Rodilla, Cristina (ENDOXA, 2002)
Lacan's enigmatic statement «it does not exist sexual relation" means that there is a logical impossibility to stablish a biunivocal relation between the elements belonging to the sets MAN and WOMAN because they are not complementary. Pulsión, that is inherent to the real register, prevents it; however, they may be complementary at the level of the imaginary register. This article aims to illustrate this point through Podeswas's film «The five senses".